REPRESENTASI ANAK WUNGŚU SEBAGAI PENGUASA KERAJAAN BALI KUNO - Hedwi Prihatmoko; Wanny Rahardjo Wahyudi (Badan Riset dan Inovasi Nasional, 2023)
Abstract. Representation of Anak Wungśu as the Ruler of the Ancient Balinese Kingdom. Representation is the process by which cultural agents use language, in a broad sense, to produce meaning, while meaning is created to represent a concept. Ancient Indonesian kings, including ancient Balinese kings, also engaged in the production of meaning to represent themselves, one of which was through inscriptions. King Anak Wungśu had a distinct portrayal as a king compared to his predecessors, particularly in the title used to address him. Nevertheless, the representation of an ideal king remained constructed around the figure of Anak Wungśu. There are three aspects to consider regarding the process of meaning production in Anak Wungśu’s inscriptions, namely the world of things, the conceptual world, and the signs. The data used are transcriptions of old Balinese inscriptions, research findings, and other scientific works related to epigraphy. Analysis was done by sorting, grouping, and translating the information within the inscriptions to provide an overview of the world of things, the conceptual world, and signs. The study in this article indicates that the representation of the ideal king of Anak Wungśu was constructed based on the concept of aṣṭabrata and his self-association with gods. The representation of this ideal king was also built through his policies as a manifestation of applying aṣṭabrata during his reign. Keywords: Inscription, Bali, Ancient History, Representation, Anak Wungśu, Ideal King, Aṣṭabrata. Abstrak. Representasi adalah proses ketika pelaku budaya menggunakan bahasa, dalam arti yang luas, untuk memproduksi makna, sedangkan makna diproduksi untuk mewakili suatu konsep. Raja-raja pada masa Indonesia Kuno, termasuk raja Bali Kuno, juga melakukan produksi makna untuk merepresentasikan dirinya, salah satunya melalui prasasti. Raja Anak Wungśu memiliki penggambaran yang berbeda sebagai seorang raja jika dibandingkan dengan raja-raja pendahulunya, terutama dalam penyebutan gelarnya. Kendati demikian, representasi sebagai raja ideal masih tetap terbangun pada sosok Anak Wungśu. Terdapat tiga aspek yang perlu diperhatikan terkait proses produksi makna di dalam prasasti Raja Anak Wungśu, yaitu dunia realitas, dunia konseptual, dan tanda. Data yang digunakan berupa transkripsi prasasti Bali kuno, hasil penelitian, dan karya ilmiah lain yang berkaitan dengan bidang epigrafi. Analisis berupa pemilahan, pengelompokan, dan penerjemahan keterangan-keterangan dalam prasasti dilakukan untuk memberikan gambaran terkait dunia realitas, dunia konseptual, dan tanda. Kajian dalam artikel ini menunjukkan bahwa representasi raja ideal dari Anak Wungśu dibangun berdasarkan konsep aṣṭabrata dan pengasosiasian diri dengan dewa. Representasi raja ideal itu dibangun juga melalui kebijakan-kebijakannya sebagai bentuk penerapan aṣṭabrata di dalam kehidupan bernegara. Kata kunci: Prasasti, Bali, Sejarah Kuno, Representasi, Anak Wungśu, Raja Ideal, Aṣṭabrata.